Infection by gymnophallid metacercariae enhances predation mortality of SW Atlantic stout razor clam Tagelus plebeius - Addino, Mariana del Sol (2010)
Parasite life cycles are frequently completed in different hosts, thus the parasites have its life cycle overlapped to natural trophic webs. The family Gymnophallidae (Class: Trematoda; Subclass: Digenea) includes digenetic parasites whose larval stages occur on bivalves and may affect bivalve predation by the final host of these parasites. In this work we evaluated: (a) if individuals of the razor clam Tagelus plebeius with higher parasite intensity suffer higher predation by the oystercatcher Haematopus palliatus and, (b) if there is any effect of parasite intensity on burrowing and escape behaviours of these razor clams which may enhance exposure to predators. Field experiments (oystercatcher exclusion vs. open access) showed that clams with higher parasite intensity support higher predation by oystercatchers, which suggests a higher consumption of more parasitized clams and thus, a more successful reproduction of parasites linked to the intensity of infection. However, clam burrowing and escape behaviours did not show differences related to different parasite intensity, suggesting that the commonly believed mechanisms are not responsible in this case.